Efektivitas Pendistribusian Dana Zakat Di Inisiatif Zakat Indonesia Perwakilan Bengkulu Dengan Pendekatan Zakat Core Principle - Yanto, Muhammad Pebri; Asnaini, Asnaini; Harpepen, Andi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
This study aims to find out how zakat funds are distributed and the effectiveness of zakat fund distribution at the Inisiatif Zakat Indonesia (IZI )Perwakilan Bengkulu. This research is field research using a descriptive qualitative approach. Data collection methods were carried out by conducting interviews, observation and documentation. The data analysis technique uses the Miles and Huberman model, namely data reduction, data presentation/description, and drawing conclusions. The results of the research obtained are first: The distribution of zakat funds at IZI Perwakilan Bengkulu Representative is distributed to all mustahik groups except slaves. The IZI Perwakilan Bengkulu Representative Program is: education, health, humanity, da'wah and economic sector programs. Second, the effectiveness of distributing zakat funds at the IZI Perwakilan Bengkulu using the Zakat Core Principle (ZCP) is in two categories, namely by calculating the Disbursement Collection Ratio (DCR) and Time Speed. The calculation according to the DCR in 2021 is 64%, in 2022 it is 81%, and in 2023 it is 68% so it is in the effective DCR category. This means that the IZI Perwakilan Bengkulu Representative has distributed effectively both in terms of the DCR ratio and the speed of distribution time which is in the fast category